Differences in Outcomes between Patellar Dislocations Managed in Emergent versus Non-Emergent Care Settings - Cook, Chad E.; Saad, Mohammad; Tucker, Christopher J.; Min, Kyong S.; Westrick, Richard B.; Rhon, Daniel I. (The Journal of Knee Surgery, 2022)
Patellar dislocations occur at a much higher rate in military than civilian populations. Past population-level studies have shown that surgical management is as good as or superior to conservative care and may reduce future reoccurrences. Although in acute cases and in civilian clinics, patellar dislocations are usually managed first in an emergent care setting, previous work suggests this can lead to increased costs. This study compared differences in downstream care type and intensity of services based on whether initial care occurred in emergent or non-emergent care settings. In our sample of 1,523 Military Health System (MHS) beneficiaries with patellar dislocation and 2-year follow-up, we found non-significant differences in costs, intensity of services, and rates of surgical repair regardless of whether the patient was initially seen in an emergent versus non-emergent care setting. Although we found significant increases in the use of imaging, patellar dislocation-related medical visits, and frequency of closed treatment approaches in emergent care settings, these values were very small and likely not clinically significant. These findings, which included all the patellar dislocations reported across the entire MHS in a 24-month period, suggest that neither emergent nor non-emergent care settings are likely to influence the long-term care received by the individual.
Keywords: patellofemoral pain syndrome; physical therapy; dislocation; military medicine